The Production and Processing of Inorganic Materials - Evans, James; De Jonghe, Lutgard (The Minerals, Metals & Materials Series, 2016)
Guiding readers from the significance, history, and sources of materials to advanced materials and processes, this textbook looks at the production and primary processing of inorganic materials, such as ceramics, metals, silicon, and some composite materials. The text encourages instructors to teach the production of all types of inorganic materials as one. While recognizing the differences between producing various types of materials, the authors focus on the commonality of thermodynamics, kinetics, transport phenomena, phase equilibria and transformation, process engineering, and surface chemistry to all inorganic materials. The text focuses on fundamentals and how fundamentals can be applied to understand how the major inorganic materials are produced and the initial stages of their processing. Understanding of these fundamentals will equip students for engineering future processes for producing materials or for studying the processing of the many less common materials not examined in this text. The text is intended for use in an undergraduate course at the junior or senior level, but will also serve as a useful introductory and reference work for graduate students and practicing scientists and engineers.